2021
DOI: 10.1101/2021.08.12.456067
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Paramecium Polycomb Repressive Complex 2 physically interacts with the small RNA binding PIWI protein to repress transposable elements

Abstract: Polycomb Repressive Complex 2 (PRC2) maintains transcriptionally silent genes in a repressed state via deposition of histone H3 K27 trimethyl (me3) marks. PRC2 has also been implicated in silencing transposable elements (TEs) yet how PRC2 is targeted to TEs remains unclear. To address this question, we performed tandem affinity purification combined with mass spectrometry and identified proteins that physically interact with the Paramecium Enhancer-of-zeste Ezl1 enzyme, which catalyzes H3K9me3 and H3K27me3 dep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
3
1

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 62 publications
1
1
0
Order By: Relevance
“…To determine whether the retention of TEs can be associated with transcriptional upregulation of these elements, as previously reported upon EZL1 silencing ( 37 ), we performed paired-end mRNA sequencing at late developmental stages (30–40 h after T0) in control, SPT5m and SPT4 -RNAi conditions. Our analysis revealed that expression of TEs is up-regulated during MAC development upon SPT5m -RNAi and the effect was comparable with de-repression observed for EZL1 ( Supplementary Figure S7 ) ( 50 ). On the other hand, SPT4 -RNAi resulted in a very small change in TEs expression.…”
Section: Resultssupporting
confidence: 74%
“…To determine whether the retention of TEs can be associated with transcriptional upregulation of these elements, as previously reported upon EZL1 silencing ( 37 ), we performed paired-end mRNA sequencing at late developmental stages (30–40 h after T0) in control, SPT5m and SPT4 -RNAi conditions. Our analysis revealed that expression of TEs is up-regulated during MAC development upon SPT5m -RNAi and the effect was comparable with de-repression observed for EZL1 ( Supplementary Figure S7 ) ( 50 ). On the other hand, SPT4 -RNAi resulted in a very small change in TEs expression.…”
Section: Resultssupporting
confidence: 74%
“…However, only a minor fraction of IESs depend on the scnRNA pathway (Furrer et al, 2017; Lhuillier‐Akakpo et al, 2014). The elimination process in the new developing MAC is initiated either by the interaction of the scnRNA with a nascent transcript or the DNA itself (Pina et al, 2021). In brief, IES targeted by scnRNAs become excised by the domesticated piggyBac transposase called piggyMac.…”
Section: Selective Hybridization Is Used Differently For Genome Scann...mentioning
confidence: 99%